Essential oils biological activity of the Lippia alba (Verbenaceae) shrub - Ortega Cuadros, Mailen; Acosta de Guevara, Emma E; Molina Castillo, Ailen D; Gutiérrez Castañeda, Clara; Castro Amarís, Glorismar; Tofiño-Rivera, Adriana P (Revista de Biología Tropical, 2020)
Introduction: Lippia alba is an aromatic species belonging to the Verbenaceae family. Its essential oils have been used in different industries, because of its biological properties. Objective: Identify the perspectives of the biotechnological applications of Lippia alba essential oils. Methodology: A scoping review was conducted on the biological activity of Lippia alba essential oils registered until October, 2018 in EBSCO, Embase, Scopus, and Lilacs databases. Results: Chemotypes I and III have been reported for different biological activities from the evaluations performed on microorganisms, fish, arthropods, small mammals, and cell lines; fundamentally associated with antibacterial, antifungal, cytotoxic, antioxidant, and sedative effects, among others. Records focused mainly on the health, fishing industry, and agrifood sectors. Conclusion: Studies on the effect of essential oil are promising, but do not reflect a continuity of the research toward prototypes or finished commercial products. Research groups must unify evaluation methodologies and include in all studies the relationship between phytochemical and biological activity for the meta-analyses to be possible. Likewise, they must join efforts through the National System for Agricultural Innovation (SNIA, for the term in Spanish) to generate finished products that impact upon society and facilitate progress in the country’s bio-economy.